Bisphenol A exposure disturbs the bone metabolism : An evolving interest towards an old culprit - Thent, Zar Chi; Froemming, Gabriele R.A.; Muid, Suhaila (Elsevier Inc., 2018)
Bisphenol A (BPA) (2,2,-bis (hydroxyphenyl) propane), a well-known endocrine disruptor (ED), is the exogenous chemical that mimic the natural endogenous hormone like oestrogen. Due to its extensive exposure to humans, BPA is considered to be a major toxicological agent for general population. Environmental exposure of BPA results in adverse health outcomes including bone loss. BPA disturbs the bone health by decreasing the plasma calcium level and inhibiting the calcitonin secretion. BPA also stimulated differentiation and induced apoptosis in human osteoblasts and osteoclasts. However, little is known about the underlying mechanisms of the untoward effect of BPA against bone metabolism. The present review gives an overview on the possible mechanisms of BPA towards bone loss. The previous literature shows that BPA exerts its toxic effect on bone cells by binding to the oestrogen related receptor-gamma (ERγ), reducing the bone morphogenic protein-2 (BMP-2) and alkaline phosphatase (ALP) activities. BPA interrupts the bone metabolism via RANKL, apoptosis and Wnt/β-catenin signaling pathways. It is, however, still debated on the exact underlying mechanism of BPA against bone health. We summarised the molecular evidences with possible mechanisms of BPA, an old environmental culprit, in bone loss and enlightened the underlying understanding of adverse action of BPA in the society. © 2018 Elsevier Inc.